Ergonomics and stress at workplace: engineering contributions to social sciences - Zafir Mohd Makhbul; Nor Liza Abdullah; Zizah Che Senik (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present study explores ergonomic workstation factors to explain work stress outcomes. Proportionate stratified random sampling method is utilized to collect data from 500 production operators. The production operators are employees of 11 manufacturing electronics organizations that joined Malaysian International Chamber of Commerce and Industry (MICCI). The data samples are based upon self-administered questionnaires. Following data analysis, ergonomically designed workstations are proven to be a significant strategy to help organizations minimize work stress outcomes. Additionally, the multiple regression analysis shows that ergonomic workstation element collectively has significant relationship with work stress outcomes.